Lower Limb Osteochondrosis and Apophysitis in Young Athletes—A Comprehensive Review - Krystian Maruszczak; Tomasz Madej; Piotr Gawda (Applied Sciences)
Osteochondrosis and apophysitis are common causes of pain in the growing skeleton, each with different causes and treatment approaches. Osteochondrosis involves degenerative processes affecting the epiphyseal ossification centers of the developing bones, while apophysitis results from repetitive traction injuries to the tendon insertions and affects both the cartilage and the underlying bone. Raising awareness of these conditions is crucial to facilitate the recovery of young athletes and prevent their sporting careers from being jeopardized early on. This review presents six known lower limb conditions that occur in young athletes, including three apophysitis such as Osgood–Schlatter disease, Sinding–Larsen–Johansson syndrome, and Sever’s disease, and three osteochondroses, including Perthes’ disease, Köhler’s disease, and Freiberg’s disease. The aim of this review is to outline the pathophysiology, clinical presentation, and treatment strategies for each of these conditions to provide a comprehensive understanding of their impact on young athletes. This review will provide clinicians, coaches, and physiotherapists with essential, evidence-based insights to increase their awareness of these conditions and refine treatment strategies for young athletes.